DAMPAK FERTILITAS TERHADAP KEBUTUHAN DASAR KELUARGA (Studi Kasus Pada Keluarga Dengan Jumlah Anak Lebih dari Dua di Desa Pondok Kelapa, Kabupaten Bengkulu Tengah) - Heri Sunaryanto (Jurnal Sosiologi Nusantara, 2015)
The aim of this study was to analyze the impact of high fertility on the fulfillment of basic needs in Central Bengkulu Regency. This research is quantitative descriptive with the number of respondents was 50 people. The analytical method used was SPSS (Statistic Program for Sosial Sciences) with cross tabulation analysis and triangulation. The results showed that there was no relationship between the number of children and the fulfillment of basic needs such as education, fulfillment of food, shelter and health. There are several reasons of the explanation of the social reality. Furthermore, from the people perspective high fertility level is more linked to social values of children than of the calculation based on the fulfillment of basic needs.Keywords: Impact Fertility, Education, Housing, Food and Health.